Impact of staggered transplanting of pollen parents and repeated pollinationmethods in hybrid seed production of marigold (Tagetes erecta L.) - Veeresh Kumar, R; Bharathi, T U; Hima Bindu, K; Laxman, R H; Venugopalan, R; Reddy, P V R; Prakash, Tejaswini (Journal of Horticultural Sciences, 2025)
Marigold is an important commercial flower crop of India and hybrids are in demand. However, the hybrid seeds are being imported due to the limited number of hybrids. Seed production of F1 hybrids needs to be enhanced to reduce the dependency on imported seeds. Therefore, the present study was initiated to work out the strategies for maximizing the hybrid seed production in four hybrid combinations. Seed parents exhibited delayed flowering with an extended duration ranging from 104.89 to 114.50 days, in contrast to the early-flowering pollen parents, which had a shorter flowering duration of 65.39 to 72.28 days. This discrepancy could be effectively addressed by staggered planting of pollen parents at multiple intervals, ensuring consistent pollen availability throughout the active flowering period of the seed parents. Irrespective of the hybrid combinations, repeated pollination for three-time registered higher seed setting percentage (49.56%), more number of seeds (112.79) and higher seed weight (250.67 mg) per flower compared to either one or two time pollinations. The study highlighted the potential for enhanced hybrid seed production through staggered planting of pollen parents combined with repeated pollination, ensuring maximum seed set per flower and optimizing seed yield per unit area of production.